THE ROLE OF “DETECTIVE DOCTORS” IN EXPOSING THE SKINCARE MAFIA: HEALTH COMMUNICATION TO RAISE PUBLIC AWARENESS - Talitha Carlen Anora Junus (PT. Jurnal Center Indonesia Publisher, 2026)
The beauty and skincare industry in Indonesia is growing rapidly and promising. However, behind this growth, there has been a revelation of numerous ingredients in skincare products that do not match their claims, with many containing harmful substances such as mercury, hydroquinone, and more. This issue began to surface when a beauty doctor, often referred to as the